Ultrasonographic Assessment of Renal Length with Respect to Age and Sex: A Hospital Based Study - Gupta, Anil Kumar; Baral, Lekhanath; Shah, Gaurav Jung (Journal of Nepalgunj Medical College, 2022)
Introduction: Kidney is an important retroperitoneal organ with excretory and endocrine functions. The length of kidney is affected in variety of clinical disorders with age. Aims: The aim of the study was to determine the renal length with respect to individual’s sex and age. Methods: This study was conducted on 369 patients referred to department of Radiology for abdominal ultrasonographic examination where renal length was measured and recorded. Results: The mean right kidney length was found to be 9.3403 cm and the left mean kidney length was found to be 9.3490 cm. In comparison among male and female, males were found to have a greater mean kidney length. The maximum mean right kidney length was found in 50-59 years age groups while left kidney length was found maximum in 30-39 years age group. Conclusion: We performed ultrasonographic assessment of renal length with respect to age and sex in Nepalese population. We found that the kidney length of both left and right kidneys was related to age and sex.